Análise da precipitação pluviométrica e estimada por radar meteorológico na Amazônia oriental - CAMPOS, Amanda Souza (2019)
This study aimed to analyze and characterize the variability of monthly and daily rainfall observed by rain gauges and weather radar estimated from the eastern Amazon, during the months of February and July, for city and area of forest, because these areas have contrasting landscapes, responding differently in quantitative precipitation for both the rainy season, and for the dry season, regardless of the weather system active. Thus, the quantitative evaluation of the monthly precipitation was performed by using the climatological normal INMET to areas of the city and IBAMA for forest area compared to the monthly cumulative, where urban areas have a higher quantity of rain relation to forest area, both for the rainy season and dry season for the period. In analyzing the accumulated daily precipitation events were selected for heavy rains, which analyzed meteorological parameters in combination with weather radar reflectivity, where the reflectivity was treated and viewed through the TITAN software and converted into millimeters by Marshall and Palmer relationship (1948), where the information given by weather radar data collected to collude by rain gauges.